2012
DOI: 10.2310/8000.2012.120526
|View full text |Cite
|
Sign up to set email alerts
|

The safety of ethanol infusions for the treatment of methanol or ethylene glycol intoxication: an observational study

Abstract: Background: Methanol or ethylene glycol ingestion may result in significant morbidity or death without prompt treatment. Despite traditional and widespread use of intravenous ethanol as an antidote, its safety is not well described. An evaluation of the safety and ease of titrating ethanol infusions is necessary given the availability of an alternative antidote. Objective: To evaluate the safety and ease of titrating ethanol infusions for the treatment of methanol or ethylene glycol ingestion. Methods: We revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…In one study, it was shown that complications of ethanol infusion in children were uncommon [ 121 ]. However, in another review of 49 adults treated with ethanol infusions, 92% of patients had at least one adverse event [ 122 ]. When intensive monitoring is unavailable, prescribing ethanol orally is also effective, especially when the patient is taken to hospital late.…”
Section: Treatmentmentioning
confidence: 99%
“…In one study, it was shown that complications of ethanol infusion in children were uncommon [ 121 ]. However, in another review of 49 adults treated with ethanol infusions, 92% of patients had at least one adverse event [ 122 ]. When intensive monitoring is unavailable, prescribing ethanol orally is also effective, especially when the patient is taken to hospital late.…”
Section: Treatmentmentioning
confidence: 99%
“…Adverse events and difficulty in maintaining therapeutic concentrations of ethanol have previously been reported in other studies. 8,9 Nevertheless, the outcome was generally favourable, irrespective of the antidote used, even in a subgroup of patients with more severe symptoms (PSS 2-3). Although some benefits were seen with fomepizole in a study involving dogs 10 , there have been no randomised controlled trials comparing fomepizole with ethanol in humans but a recent systematic review concluded that there are no significant differences in outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Though some authors ask for considering the safety profile and therapeutic drug monitoring when choosing ethanol as antidote for methanol [25] , many authors found ethanol administration effective and safe in management of patients with methanol poisoning [24] .…”
Section: Discussionmentioning
confidence: 99%